Water level control system (software development) / Ahmad Zaidi Hassan - Hassan, Ahmad Zaidi (1996)
Level control is widely used in chemical, oil and gas plant. Without controller. The product has low quality. By using the controller, such as Programmable Logic Controller (PLC), micro controller or personal computer, the quality of the product easy to maintain. Personal computer is the most powerful tooi for this application. The available of low cost computers places a powerful tooi to monitor, control and improve the quality. This thesis provide the theory of analogue to digital and digital to analogue conversion and their applications.